Introducing a Model of Human-Social Infrastructure Enabling Knowledge Management Practices - Abbas Monavvarian; Mohammad Mousakhani; Peyman Akhavan; Nasser Asgari (Journal of Information Technology Management)
In the knowledge-based era knowledge management (KM) is considered as the primary task of organizations that strive to utilize of their intellectual capitals effectively. Hence it is vital to understand carefully the appropriate contexts and enablers of knowledge management practices. Human- social factors are among most influential factors that their effects are as important as structural and technological enablers. In spite of these vital effects, their role has not been studied sufficiently. This article tries to explore the simultaneous effects of the human capital, social capital and cultural capital on the effectiveness of knowledge management practices. It will investigate the way in which these intellectual capitals can enforce attitudes and behaviors required for implementing KM effectively. The population of the research consists of 950 person of managers and senior experts of the NIOPDC. A sample of 270 subjects was selected as statistical sampling. According to the research findings, these human-social factors have a considerable effect on the effectiveness of KM. These findings support the necessity of adopting a more humanistic approach for implementing knowledge management more effectively.